Transnational aging and reconfigurations of kin work - Dossa, Parin Aziz, 1945-; Coe, Cati (Global perspectives on aging series., 2017)
"Transnational Aging and Reconfigurations of Kin Work documents the social and material contributions of older persons to their families in settings shaped by migration, their everyday lives in domestic and community spaces, and in the context of intergenerational relationships and diasporas. Much of this work is oriented toward supporting, connecting, and maintaining kin members and kin relationships--the work that enables a family to reproduce and regenerate itself across generations and across the globe"--